Circulating biomarkers for monitoring therapy response and detection of disease progression in lung cancer patients. (2021) - de Kock, Remco; Borne, Ben van den; Soud, Maggy Youssef- El; Belderbos, Huub; Stege, Gerben; de Saegher, Marleen; van Dongen-Schrover, Claartje; Genet, Sylvia; Brunsveld, Luc; Scharnhorst, Volkher; Deiman, Birgit
Highlights: Serial testing of ctDNA could complement radiographic therapy response monitoring and guide the imaging frequency of lung cancer patients ctDNA and Cyfra21-1 are relevant biomarkers for therapy response monitoring in lung cancer patients Ca125 might be a useful biomarker for therapy response monitoring in lung cancer patients Abstract: Liquid biopsies have become of interest as minimally invasive ways to monitor treatment response in lung cancer patients. Circulating tumor DNA (ctDNA) and protein biomarkers are evaluated for their added value in monitoring therapy response and early detection of disease progression. Plasma and serum samples of non-small cell or small cell lung cancer patients were analyzed for driver mutations in ctDNA ( EGFR, KRAS or BRAF ) using droplet digital PCR and protein biomarkers (CA125, CEA, CA15.3, Cyfra 21-1, HE4, NSE, proGRP and SCCA) using electrochemiluminescence immunoassays. Biomarker concentration changes were compared with the outcome of CT-scans during therapy. The median difference of the concentration of ctDNA, CA125 and Cyfra21-1 was significantly lower in patients with partial response (PR) compared to patients with progressive disease (PD) on the first evaluation CT-scan (P<0.001, P=0.042 and P=0.020, respectively). A substantial agreement between ctDNA or CA125 response and radiographic response was observed (k=0.692 and k=0.792, respectively). The median difference of the concentration of ctDNA and Cyfra21-1 was also significantly lower in PR patients compared to PD patients at the last CT-scan during therapy (P<0.001 and P=0.026, respectively). An almost perfect agreement between ctDNA and radiographic response (k=0.827) and a moderate agreement between Cyfra21-1 response and radiographic response was observed (k=0.553). Serial testing of the concentration of ctDNA, Cyfra21-1, and possibly CA125 could be a useful added tool for monitoring therapy response and early detection of disease progression in lung cancer patients.